Urea-Fibrinogen Slide Coagulase Test – A Simple Alternative Method for the Rapid Identification of Staphylococcus aureus - Sharma, Binita Koirala; Gokhale, S; Sharma, K (Journal of Gandaki Medical College-Nepal, 2017)
Introduction: The accurate identification of Staphylococcus aureus clinical isolates requires a series of tests. Morphological features and slide coagulase test are two criteria on which S. aureus are identified. Resort to tube coagulase test is sought when results of slide coagulase test are equivocal or doubtful. Both coagulase tests detect the enzymes that convert fibrinogen into fibrin. Human, rabbit or sheep pooled plasma is used as substrate for both tests. Slide coagulase test is simpler and faster as compared to tube coagulase test. The plasma could be carrier of many human and animal pathogens like HIV, HBV, HCV etc. Storage of plasma for longer duration is fraught with chances of contamination. Improperly stored plasma can lead to false positive or negative results. Citrated plasma may be unsuitable for this test if contaminated with citrate utilizing bacteria. Considering the role of S. aureus as a common etiological agent in nosocomial and community infections, there is a need of implementing rapid, easy and cost-effective phenotypic test. Objectives: Considering the disadvantages and risks associated with fresh plasma, this study aims to launch for safer, more reliable substitute with longer shelf life that may provide reliable results for prompt identification of S. aureus by slide coagulase test. Methods: The present work evaluates slide coagulase test (SCT), and urea fibrinogen slide coagulase test (UF-SCT) for S. aureus detection considering Tube coagulase test (TCT) as the reference method. Sensitivity, specificity, positive predictive value and negative predictive values of SCT and UF-SCT were calculated using TCT as gold standard. Results: A total of 150 staphylococcal isolates from different clinical specimens ere selected for the evaluation of coagulase tests. All the specimens were subjected to SCT, UF-SCT and TCT. The UF-SCT showed better sensitivity (95.04%), specificity (100%), PPV (100%), and NPV (82.85%) with reference to TCT. UF-SCT showed similar sensitivity and specificity to SCT. None of the isolates were negative in UF-SCT and positive in SCT. Since UF-SCT does not incorporate plasma directly and at the same time has a very good sensitivity and specificity, it is recommended that UF-SCT could replace SCT for identification of S. aureus. Conclusion: The findings of present study shall encourage laboratories to use the urea-fibrinogen slide coagulase test routinely for the rapid identification of S aureus. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 5-10